Peptide YY (1–36) peptides from phylogenetically ancient fish targeting mammalian neuropeptide Y1 receptors demonstrate potent effects on pancreatic β‐cell function, growth and survival. Issue 3 (9th December 2019) - Lafferty, Ryan A.; Tanday, Neil; McCloskey, Andrew; Bompada, Pradeep; De Marinis, Yang; Flatt, Peter R.; Irwin, Nigel
Abstract: Aim: To investigate the antidiabetic efficacy of enzymatically stable Peptide YY (PYY) peptides from phylogenetically ancient fish. Materials and methods: N‐terminally stabilized, PYY (1–36) sequences from Amia calva (bowfin), Oncorhynchus mykiss (trout), Petromyzon marinus (sea lamprey) and Scaphirhynchus albus (sturgeon), were synthesized, and both biological actions and antidiabetic therapeutic efficacy were assessed. Results: All fish PYY (1–36) peptides were resistant to dipeptidyl peptidase‐4 (DPP‐4) degradation and inhibited glucose‐ and alanine‐induced ( P < 0.05 to P < 0.001) insulin secretion. In addition, PYY (1–36) peptides imparted significant ( P < 0.05 to P < 0.001) β‐cell proliferative and anti‐apoptotic benefits. Proliferative effects were almost entirely absent in β cells with CRISPR‐Cas9‐induced knockout of Npyr1 . In contrast to human PYY (1–36), the piscine‐derived peptides lacked appetite‐suppressive actions. Twice‐daily administration of sea lamprey PYY (1–36), the superior bioactive peptide, for 21 days significantly ( P < 0.05 to P < 0.001) decreased fluid intake, non‐fasting glucose and glucagon in streptozotocin (STZ)‐induced diabetic mice. In addition, glucose tolerance, insulin sensitivity, pancreatic insulin and glucagon content were significantly improved. Metabolic benefits were linked to positive changes in pancreatic islet morphology as a result of augmented ( P < 0.001) proliferation and decreased apoptosis of β cells. Sturgeon PYY (1–36) exerted similar but less impressive effects in STZ mice. Conclusion: These observations reveal, for the first time, that PYY (1–36) peptide sequences from phylogenetically ancient fish replicate the pancreatic β‐cell benefits of human PYY (1–36) and have clear potential for the treatment of type 2 diabetes.